Solvent mixture effect in the zinc hexacyanoferrate (III) nanoparticles: Synthesis, characterization and voltammetric application - Do Carmo, Devaney Ribeiro [UNESP] (2016)
This work describes the preparation and characterization of size-controlled zinc hexacyanoferrate (III) nanoparticles (ZnH). They were prepared using different proportions of water/formamide in the complexation reaction of Zn2+ with [FeIII(CN)6]3−. The materials were characterized by Fourier Transform Infrared Spectroscopy (FT-IR), Ultraviolet-Visible Spectroscopy (UV–vis), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDX) and Cyclic Voltammetry (CV). The cyclic voltammograms of the modified graphite paste electrode with ZnH-1, ZnH-2, ZnH-3 and ZnH-4 showed a well-defined redox couple with formal potential (Eθ′) = 0.94 ± 0.01 V (ν=20 mV s−1; KCl 1.0 M)) attributed to the redox process [FeII(CN)6]/[FeIII(CN)6] in the presence of Zn2+. The dependence of particle size on the detection of sulfite was verified.